Study on the Properties and Pore Structure of Geopolymer Foam Concrete Incorporating Lead–Zinc Tailings - Yifan Yang; Ming Li; Qi He; Chongjie Liao (Buildings)
Geopolymer foam concrete (GFC) is a green, lightweight material produced by introducing bubbles into the geopolymer slurry. The raw materials for GFC are primarily silicon–aluminum-rich minerals or solid waste. Lead–zinc tailings (LZTs), as an industrial solid waste with high silicon–aluminum content, hold significant potential as raw materials for building materials. This study innovatively utilized LZTs to prepare GFC, incorporating MK, GGBS, and alkali activators as silicon–aluminum-rich supplementary materials and using H2O2 as a foaming agent, successfully producing GFC with excellent properties. The effects of different LZT content on the pore structure and various macroscopic properties of GFC were comprehensively evaluated. The results indicate that an appropriate addition of LZT effectively optimizes the pore structure, resulting in uniform pore distribution and pore shapes that are more spherical. Spherical pores exhibit better geometric compactness. The optimal LZT content was determined to be 40%, at which the GFC exhibits the best compressive strength, thermal conductivity, and water resistance. At this content, the dry density of GFC is 641.95 kg/m3, the compressive strength reaches 6.50 MPa after 28 days, and the thermal conductivity is 0.176 (W/(m·K)). XRD and SEM analyses indicate that under the combined effects of geopolymerization and hydration reactions, N–A–S–H gel and C–S–H gel were formed. The preparation of GFC using LZTs shows significant potential and research value. This study also provides a feasible scheme for the recycling and utilization of LZTs.